The role of home care in the management of hypertension in the elderly - Hijrah Hijrah; Suprapto Suprapto; Darmi Arda; Wibowo Wibowo (Jurnal Edukasi Ilmiah Kesehatan, 2025)
Introduction: Hypertension is a significant health problem in the elderly that can increase the risk of cardiovascular disease. Home care has the potential to improve hypertension management in this population. This study aims to evaluate the effectiveness of home care in managing hypertension in the elderly. Materials and Methods: This study uses a mixed-methods design with quantitative and qualitative approaches. Quantitatively, quasi-experimental studies were carried out with intervention and control groups. The intervention group received home care services, including education, blood pressure monitoring, and medication adherence support. The control group received standard treatment. Blood pressure data were measured at the beginning of the study. Qualitatively, in-depth interviews were conducted with the elderly and home care nurses to understand their experiences and perceptions. Results: Quantitative results showed a significant decrease in systolic and diastolic blood pressure in the intervention group compared to the control group after 6 months (p < 0.05). Qualitative results revealed that the elderly felt more motivated and better-understood hypertension management thanks to home care support. Home care nurses also reported increased medication adherence and positive lifestyle changes in the elderly. Conclusions: Home care is effective in improving hypertension management in the elderly. These services provide comprehensive support, including education, monitoring, and motivation, which contribute to lowering blood pressure and improving the quality of life of the elderly